2013
DOI: 10.1016/j.nicl.2013.10.009
|View full text |Cite
|
Sign up to set email alerts
|

EEG and Neuronal Activity Topography analysis can predict effectiveness of shunt operation in idiopathic normal pressure hydrocephalus patients

Abstract: Idiopathic normal pressure hydrocephalus (iNPH) is a neuropsychiatric syndrome characterized by gait disturbance, cognitive impairment and urinary incontinence that affect elderly individuals. These symptoms can potentially be reversed by cerebrospinal fluid (CSF) drainage or shunt operation. Prior to shunt operation, drainage of a small amount of CSF or “CSF tapping” is usually performed to ascertain the effect of the operation. Unfortunately, conventional neuroimaging methods such as single photon emission c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 53 publications
2
37
0
Order By: Relevance
“…Allali et al, using the walking test in dual task conditions, have reported that after CSF tapping iNPH patients significantly improved allocation of attention to gait during dual task 21 , which is a function of right VAN 17 22 , compared to iNPH-like patients. Also, in a previous study, we found that alpha and beta NPV changes at the right anterior prefrontal electrode (Fp2) correlated with changes in walking time, which suggests a recruitment of the right VAN in gait control in iNPH patients 8 . This recruitment of VAN during gait has also been seen in patients with Parkinson's disease, and these authors discussed that an associated burn-out of VAN may lead to the freezing of gait 23 .…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Allali et al, using the walking test in dual task conditions, have reported that after CSF tapping iNPH patients significantly improved allocation of attention to gait during dual task 21 , which is a function of right VAN 17 22 , compared to iNPH-like patients. Also, in a previous study, we found that alpha and beta NPV changes at the right anterior prefrontal electrode (Fp2) correlated with changes in walking time, which suggests a recruitment of the right VAN in gait control in iNPH patients 8 . This recruitment of VAN during gait has also been seen in patients with Parkinson's disease, and these authors discussed that an associated burn-out of VAN may lead to the freezing of gait 23 .…”
Section: Discussionsupporting
confidence: 51%
“…More specifically, improvement of walking time attributed to CSF tapping correlated with an alpha NPV decrease in the supplementary motor area (SMA) and alpha and beta NPV decreases in the prefrontal cortices (PFC), especially in the right anterior PFC. In addition, gait status recovery correlated with delta and alpha NPV decreases in the left dorsal premotor area (PMA), and attention recovery correlated with an alpha NPV decrease in the right dorsolateral PFC (DLPFC) 8 . These findings demonstrated the important involvement of the right anterior PFC and premotor cortex to gait improvement induced by CSF tapping in iNPH patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…NAT is a novel analysis method that measures EEG normalized power variance (NPV), an index of waveform complexity [76]. This method has been used successfully to detect changes in the complexity of signal dynamics associated with cognitive and clinical improvement in patients with normal pressure hydrocephalus who respond to shunt operation [77]. It was also reported that an NPV decrease represents the stabilization of cortical electrical activity which reflects functional improvement, while an NPV increase represents the destabilization of cortical electrical activity which reflects functional worsening [77].…”
Section: Eeg Signal Complexity and Agingmentioning
confidence: 99%
“…This method has been used successfully to detect changes in the complexity of signal dynamics associated with cognitive and clinical improvement in patients with normal pressure hydrocephalus who respond to shunt operation [77]. It was also reported that an NPV decrease represents the stabilization of cortical electrical activity which reflects functional improvement, while an NPV increase represents the destabilization of cortical electrical activity which reflects functional worsening [77]. In our study, NAT results showed an increase in NPV values from younger to middle-aged subjects, and a decrease in the values from middle-aged to the elderly, after an analysis of all regions and locations.…”
Section: Eeg Signal Complexity and Agingmentioning
confidence: 99%